Fibrosis-Related Biomarkers and Incident Cardiovascular Disease in Older Adults: The Cardiovascular Health Study - Agarwal, Isha (2014)
BACKGROUND: Fibrotic changes in the heart and arteries have been implicated in a diverse range of cardiovascular diseases (CVD), but whether circulating biomarkers that reflect fibrosis are associated with CVD is unknown. METHODS AND RESULTS: We determined the associations of two biomarkers of fibrosis, transforming growth factor- β (TGF-β) and procollagen type III N-terminal propeptide (PIIINP), with incident heart failure, myocardial infarction (MI), and stroke among community-living older adults in the Cardiovascular Health Study. We measured circulating TGF-β (n=1,371) and PIIINP (n=2,568) from plasma samples collected in 1996 and ascertained events through 2010. Given TGF-β’s pleiotropic effects on inflammation and fibrogenesis, we investigated potential effect modification by C-reactive protein (CRP) in secondary analyses. After adjustment for sociodemographic, clinical, and biochemical risk factors, PIIINP was associated with total CVD (hazard ratio [HR] per standard deviation [SD]=1.07, 95% confidence interval [CI]: 1.01-1.14) and heart failure (HR per SD=1.08, CI: 1.01-1.16), but not MI or stroke. TGF-β was not associated with any CVD outcomes in the full cohort, but was associated with total CVD (HR per SD=1.16, CI: 1.02-1.31), heart failure (HR per SD=1.16, CI: 1.01-1.34), and stroke (HR per SD=1.20, CI: 1.01-1.42) among individuals with CRP above the median, 2.3 mg/L (P-interaction < 0.05). CONCLUSIONS: Our findings provide large-scale, prospective evidence that circulating biomarkers of fibrosis, measured in community-living individuals late in life, are associated with CVD. Further research on whether TGF-β has a stronger fibrogenic effect in the setting of inflammation is warranted.